Charged-particle induced thermonuclear reaction rates of He-3(He-3,2p)He-4, He-3(He-4,gamma)Be-7 and Be-7(p,gamma)B-8 by using the exact tunneling probability - Yusof, N.; Abu Kassim, H. (Kluwer (now part of Springer), 2010)
The astrophysical S-factor of the experimental cross section data of the main reactions in the proton proton chain, i.e. He-3(He-3,2p)He-4, He-3(He-4,gamma)Be-7 and Be-7(p,gamma)B-8, are reanalyzed by using the exact tunneling probability in nuclear reactions. Our goal is to test this treatment in finding the reaction rate per pair for non-resonant reactions. At low temperatures, the exact treatment is identical to the standard formalism but diverges at higher temperatures.